2020
DOI: 10.1017/s0022215120000067
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic visualisation of the round window during cochlear implantation

Abstract: BackgroundEndoscopes provide a magnified view of the middle ear and visualisation of hidden areas. Otoendoscopes facilitate excellent visualisation of the round window niche during cochlear implantation.ObjectiveTo compare microscopic and endoscopic visualisation of the round window membrane during cochlear implantation in 20 patients.MethodsTwenty patients who underwent cochlear implantation were included in the study. After maximum exposure of the round window, the accessibility of the round window membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 10 publications
0
6
0
5
Order By: Relevance
“…Endoscopic Cochlear Implantation Cochlear implantation is one of the new applications of endoscopes in the field of otology, but there are few case series on this topic. In a recent study, Sharma et al 28 concluded that the visualization of the round window niche improved with the use of an otoendoscope with 1.9 mm in diameter for cochleostomy and insertion of the electrode; a similar conclusion was reached in the study by Jain A et al 29…”
Section: The Ability To Visualize Past the Shaft Of Larger Surgicalmentioning
confidence: 63%
“…Endoscopic Cochlear Implantation Cochlear implantation is one of the new applications of endoscopes in the field of otology, but there are few case series on this topic. In a recent study, Sharma et al 28 concluded that the visualization of the round window niche improved with the use of an otoendoscope with 1.9 mm in diameter for cochleostomy and insertion of the electrode; a similar conclusion was reached in the study by Jain A et al 29…”
Section: The Ability To Visualize Past the Shaft Of Larger Surgicalmentioning
confidence: 63%
“…Electrodes were inserted in the ST under endoscopic guidance. In 93 CI, a PT was performed and the endoscope facilitated recognition and magnification of RW and the electrodes were placed through the facial recess 21–26 …”
Section: Resultsmentioning
confidence: 99%
“…The visibility of RW was improved and the St Thomas Scale classification changed. Even group III patients were eligible for RW cochleostomy 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations